″Scientific and Methodological Approaches to the Problem of Information Competency Formation for University Students″ - Davydova, Zh. V. (Problems of Engineer-Pedagogical Education, 2018)
The article analyses the fundamental scientific and methodological approaches to the problem of information competency formation of university students. It is proved that the main methodological backgrounds are system, information, synergetic, hermeneutic, sign-symbolic approaches. Usage of system approach allows treat the pedagogical process as a holistic phenomenon and is a basis for designing a pedagogical system. Information approach realization provides a person with obtaining and saving knowledge, preservation and transfer of information. Implementation of synergetic approach means creating conditions for choice and allowing every subject to create his individual trajectory for reaching the target, stimulating independent thinking and making responsible decisions. Hermeneutic approach allows to realize complex co-operation between knowledge and information moving the subject to the first place. Providing sign-symbolic approach into education allows to determine the main components of a certain system, its peculiarities, possibilities, the level of co-operation and co-influence.